2019
DOI: 10.1155/2019/5830201
|View full text |Cite
|
Sign up to set email alerts
|

Research of Mortar Containing Phosphorous Slag and Calcium Carbonate Nanoparticles

Abstract: Ground phosphorous slag (PS) has not been widely used in construction due to its negative effects on the early-age performances of cementitious materials. The effects of calcium carbonate nanoparticles (NC) on strength development of mortar containing high content of PS were investigated at different curing ages. The NC was incorporated at 2% as partial mass replacements for binder. Hydration products and microstructure characterization was examined by X-ray diffraction (XRD), differential thermal gravity (DTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Therefore, a greater addition of NC caused a lower fluidity of 3DPC. The change in trend may be attributed to the highly specific surface area of NC (Supit and Shaikh, 2014;Yang and Che, 2019), which would generally increase the viscosity and the yield stress of mixtures. Furthermore, due to the accelerating effects of NC on cement, additional hydration products, such as C-S-H and CH, increase the formation of the flocculation structure of cement pastes (Roussel et al, 2012).…”
Section: Fluidity Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a greater addition of NC caused a lower fluidity of 3DPC. The change in trend may be attributed to the highly specific surface area of NC (Supit and Shaikh, 2014;Yang and Che, 2019), which would generally increase the viscosity and the yield stress of mixtures. Furthermore, due to the accelerating effects of NC on cement, additional hydration products, such as C-S-H and CH, increase the formation of the flocculation structure of cement pastes (Roussel et al, 2012).…”
Section: Fluidity Evolutionmentioning
confidence: 99%
“…It was found that concrete containing NC showed a significant improvement in mechanical strength and durability performances, which can be attributed to the improved microstructure of the concrete (Yesilmen et al, 2015;Shaikh et al, 2017;Yang and Che, 2018). Thus, the use of NC to improve the performance of concrete containing a large amount of FA has gained much attention in recent years (Hemalatha et al, 2016;Long et al, 2016;Korayem et al, 2017;Yang and Che, 2019). However, the application of NC in 3DPC is extremely insufficient, although some investigations have been made regarding adopting NC in cementitious materials.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement could lead to the enhancement of the mechanical properties of the samples. Moreover, another evidence of the addition nucleation effect was the increase in the CH peaks at 2θ of 18.05°in the nanocomposites compared to those in the plain cement, thereby indicating that more CH was produced [44].…”
Section: X-ray Diffraction (Xrd) Investigationmentioning
confidence: 96%